2018
DOI: 10.33225/pec/18.76.816
|View full text |Cite
|
Sign up to set email alerts
|

In-Class and Out-of-Class Anxiety in Speaking Turkish as a Second Language

Abstract: Turkish is spoken by a large number of people in a wide geographical area and teaching Turkish as a foreign language is a subject that gains importance nowadays. This research employed a quantitative survey strategy to address the issue of anxiety in learning Turkish language in and outside the classroom. Participants were 356 students of two high schools, one college and one university in Kazakhstan. Participants were given the Second Language Speaking Anxiety Scale (SLSAS), which was analyzed with: correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…One area of emotion that has seen a particularly strong growth in interest is that of learner emotions and the crucial role they play in SLA (Dewaele 2015; MacIntyre and Vincze 2017). Foreign Language Enjoyment (FLE) and Foreign Language Classroom Anxiety (FLCA) have been found to have complex dynamic relationships with both learner-internal and contextual variables (Dewaele and Dewaele 2017; Dewaele and MacIntyre 2014, 2016Karci, Özdemir and Balta 2018) and play an important part in learners' Willingness to Communicate in the Foreign Language (FL) and in their performance in the FL . Relationships have been found to be broadly similar in FL classes in different parts of the world, including Belgium (De Smet et al 2018), China (Jin and Zhang 2018, Li 2018Li, Jiang and Dewaele 2018;Li, Dewaele and Jiang, 2019); Iran (Shirvan and Taherian 2018; Shirvan and Talebzadeh 2018); Japan (Saito et al 2018); Poland (Piechurska-Kuciel 2017), Saudi Arabia (Dewaele and Alfawzan 2018), Spain (Dewaele, Magdalena Franco and Saito 2019) and the United Kingdom (Dewaele and Dewaele 2017;Dewaele, Witney, Saito and Dewaele 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One area of emotion that has seen a particularly strong growth in interest is that of learner emotions and the crucial role they play in SLA (Dewaele 2015; MacIntyre and Vincze 2017). Foreign Language Enjoyment (FLE) and Foreign Language Classroom Anxiety (FLCA) have been found to have complex dynamic relationships with both learner-internal and contextual variables (Dewaele and Dewaele 2017; Dewaele and MacIntyre 2014, 2016Karci, Özdemir and Balta 2018) and play an important part in learners' Willingness to Communicate in the Foreign Language (FL) and in their performance in the FL . Relationships have been found to be broadly similar in FL classes in different parts of the world, including Belgium (De Smet et al 2018), China (Jin and Zhang 2018, Li 2018Li, Jiang and Dewaele 2018;Li, Dewaele and Jiang, 2019); Iran (Shirvan and Taherian 2018; Shirvan and Talebzadeh 2018); Japan (Saito et al 2018); Poland (Piechurska-Kuciel 2017), Saudi Arabia (Dewaele and Alfawzan 2018), Spain (Dewaele, Magdalena Franco and Saito 2019) and the United Kingdom (Dewaele and Dewaele 2017;Dewaele, Witney, Saito and Dewaele 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety, the online system, involvement, enjoyment, class environment, and class dynamics were found as determining factors in the learning process. Previous research has also found anxiety, particularly Foreign Language Classroom Anxiety and Foreign Language Anxiety, as one of the major factors or barriers in the learning process of foreign languages [35,54,105], alongside the lack of personal contact and communication as well as unfavourable study environments at home [106] during the pandemic. The anxiety levels in the research group differs among students and clusters and was predominantly centred around speaking anxiety and panic and around lack of confidence and initiative in providing solicited or voluntary answers.…”
Section: Discussionmentioning
confidence: 99%